2010
DOI: 10.4049/jimmunol.1000198
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activation of T Lymphocytes by Urease-Deficient Recombinant Bacillus Calmette-Guérin Producing Heat Shock Protein 70-Major Membrane Protein-II Fusion Protein

Abstract: To activate naive T cells convincingly using Mycobacterium bovis bacillus Calmette-Guérin (BCG), recombinant BCG (BCG-D70M) that was deficient in urease, expressed with gene encoding the fusion of BCG-derived heat shock protein (HSP) 70 and Mycobacterium leprae-derived major membrane protein (MMP)-II, one of the immunodominant Ags of M. leprae, was newly constructed. BCG-D70M was more potent in activation of both CD4+ and CD8+ subsets of naive T cells than recombinant BCGs including urease-deficient BCG and BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…BCG-DHTM was produced by introducing the HSP70-MMP-II fusion gene into urease-deficient BCG-⌬UT-11-3. Previously, we reported that urease-deficient rBCG that secretes a fusion protein composed of HSP70 and MMP-II from M. leprae was superior to urease-deficient BCG-⌬UT-11-3 and normal BCG that secretes the fusion protein in the activation of APCs and naive T cells and the production of memory-type T cells in mice (40). Therefore, we used only vector control BCG-261H as a control BCG in this study.…”
Section: Discussionmentioning
confidence: 99%
“…BCG-DHTM was produced by introducing the HSP70-MMP-II fusion gene into urease-deficient BCG-⌬UT-11-3. Previously, we reported that urease-deficient rBCG that secretes a fusion protein composed of HSP70 and MMP-II from M. leprae was superior to urease-deficient BCG-⌬UT-11-3 and normal BCG that secretes the fusion protein in the activation of APCs and naive T cells and the production of memory-type T cells in mice (40). Therefore, we used only vector control BCG-261H as a control BCG in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-presentation involves distinct, well-defined pathways that utilize the proteasome and ER/Golgi. [63][64][65] The proteasome plays an important role in antigen cross-presentation by cleaving intracellular proteins into small, 8-11…”
Section: Cross-presentation By Multiple Myeloma Involves the Proteasomentioning
confidence: 99%